2020
DOI: 10.4081/monaldi.2020.1251
|View full text |Cite
|
Sign up to set email alerts
|

Alternative sites of ventricular pacing: His bundle pacing

Abstract: Since its introduction right ventricular apical (RVA) pacing has been the mainstay in cardiac pacing. However, in recent years there has been an upsurge of interest in permanent His bundle pacing (HBP), given the scientific evidence of the harmful role of dyssynchronous ventricular activation, induced by RVA pacing, in promoting the onset of heart failure and atrial fibrillation. After an intermediate period in which attention was focused on algorithms aimed at minimizing ventricular pacing, with partially ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Among these, His bundle pacing (HBP), ensuring physiological electrical activation of the ventricle, has progressively attracted the interest of researchers in this field. Currently, due to an increasing number of promising results and the development of new implantation devices, HBP is becoming a feasible and reliable alternative to conventional RV apical pacing 1 . More than 30 years ago histological studies reported that the HB is divided into cords separated by collagen running in its longitudinal axis with relatively few transverse connections between them, supporting the hypothesis of a compartmentalized electrical stimulus conduction, underlying the asynchronous conduction or longitudinal dissociation in HB 2,3 .…”
Section: Introductionmentioning
confidence: 96%
“…Among these, His bundle pacing (HBP), ensuring physiological electrical activation of the ventricle, has progressively attracted the interest of researchers in this field. Currently, due to an increasing number of promising results and the development of new implantation devices, HBP is becoming a feasible and reliable alternative to conventional RV apical pacing 1 . More than 30 years ago histological studies reported that the HB is divided into cords separated by collagen running in its longitudinal axis with relatively few transverse connections between them, supporting the hypothesis of a compartmentalized electrical stimulus conduction, underlying the asynchronous conduction or longitudinal dissociation in HB 2,3 .…”
Section: Introductionmentioning
confidence: 96%
“…In recent years, we have witnessed a progressive interest of the scientific community in His bundle (HB) pacing as an alternative to RV pacing. 4 His bundle pacing is rightly considered physiological, since, unlike RV pacing, the electrical impulse travels through the normal conduction system and, therefore, does not result in ventricular electrical dyssynchrony. 3 , 4 As a result, paced ventricular complexes show morphological features that are completely superimposable to those evident in the baseline ECG.…”
Section: Introductionmentioning
confidence: 99%
“… 4 His bundle pacing is rightly considered physiological, since, unlike RV pacing, the electrical impulse travels through the normal conduction system and, therefore, does not result in ventricular electrical dyssynchrony. 3 , 4 As a result, paced ventricular complexes show morphological features that are completely superimposable to those evident in the baseline ECG. 3 - 6 Although HB pacing, in contrast to RV pacing, should not affect the ventricular repolarization phase, there are no data in the literature about the electrocardiographic diagnosis of myocardial ischemia during HB pacing.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2] His bundle pacing (HBP) has been suggested as a more physiological approach and numerous studies have reported good success rates and benefits in patients with AV nodal block, infranodal AV block, and bundle branch block. 3,4 The main limitations of HBP included technical and anatomical difficulties associated with the availability of a limited number of tools specific for HBP implantations. 5 Enlarged right atrium (RA) and ventricle have been described among the most difficult scenarios for achieving successful permanent HBP.…”
Section: Introductionmentioning
confidence: 99%
“…Right ventricular (RV) pacing has been routinely used to treat patients with atrioventricular (AV) block; however, deleterious effects of chronic RV pacing due to induced electrical and mechanical dyssynchrony have been documented 1–2 . His bundle pacing (HBP) has been suggested as a more physiological approach and numerous studies have reported good success rates and benefits in patients with AV nodal block, infranodal AV block, and bundle branch block 3,4 . The main limitations of HBP included technical and anatomical difficulties associated with the availability of a limited number of tools specific for HBP implantations 5 .…”
Section: Introductionmentioning
confidence: 99%